Analysis of the influence factor of urban heat island [UH] in Penang Island / Norasiah Razali - Razali, Norasiah (2018)
These studies are about detecting urban heat island (UHI) in Penang Island based on the Influence of population, land use change and temperature. UHI is a phenomenon that the temperatures of the urban area are hotter than the surrounding area. The aim for this study is to analysis the relationship between population, land use change and temperature to the urban heat in Penang Island. The objective of this study are to determine the place with the high temperature in Penang Island, to determine the relationship land use change and temperature to the urban heat island (UHI) in Penang Island and to assess the influence population and land surface temperature to the urban heat island (UHI) in Penang Island. This study will have used the Erdas 2014 software and ArcGIS 10.4 software to process the data. Landsat 5 TM and Landsat 7 ETM+ on year 1999 and 2016. This study also will use the population data, that data are from department of statistic. The supervise classification method will be used to detect the land use changes. The land surface temperature (LST) will calculate in this study.